Clarification of the status of the types of Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae) described before 1950 - Allsopp, Peter G. (Zootaxa, 2020)
The status of the primary and sometimes secondary types of each of the species-level names within the Australian Melolonthini (Coleoptera: Scarabaeidae: Melolonthinae) described by Ernst Germar, Hermann Burmeister, Charles Blanchard, William Macleay, Charles Waterhouse, Thomas Blackburn, Ernst Brenske, Anton Nonfried, Julius von Moser, Arthur Olliff, Arthur Lea, Gilbert Arrow, and Alexandre Girault are clarified. Lectotypes are designated for Antitrogus nigricornis Blackburn, 1911 (= Antitrogus tasmanicus (Burmeister, 1855)), Holophylla australis Blackburn, 1888 (Rhopaea australis), Holophylla furfuracea Burmeister, 1855 (Pseudholophylla furfuracea), Lepidioderma glaber Brenske, 1895 (= Dermolepida lixi (Nonfried, 1894)), Lepidioderma lansbergei Brenske, 1895 (= Dermolepida albohirtum (Waterhouse, 1875)), Lepidioderma waterhousei Brenske, 1895 (= Dermolepida albohirtum (Waterhouse, 1875)), Lepidiota bovilli Blackburn, 1912 (= Lepidiota rothei Blackburn, 1888), Lepidiota caudata Blackburn, 1890, Lepidiota darwini Blackburn, 1888 (= Lepidiota squamulata Waterhouse, 1875), Lepidiota deceptrix Blackburn, 1912 (= Lepidiota negatoria Blackburn, 1912), Lepidiota degener Blackburn, 1888, Lepidiota delicatula Blackburn, 1888, Lepidiota frenchi Blackburn, 1912, Lepidiota gilesi Blackburn, 1912, Lepidiota grata Blackburn, 1890, Lepidiota koebelei Blackburn, 1912 (= Lepidiota rothei Blackburn, 1888), Lepidiota laevis Arrow, 1932, Lepidiota leai Blackburn, 1912 (= Lepidiota squamulata Waterhouse, 1875), Lepidiota negatoria Blackburn, 1912, Lepidiota oblonga Brenske, 1900, Lepidiota perkinsi Blackburn, 1912, Lepidiota platyura Lea, 1924 (= Lepidiota podicalis Moser, 1913), Lepidiota rubrior Blackburn, 1912, Lepidiota rufa Blackburn, 1888, Lepidiota rugosipennis Lea, 1924 (= Lepidiota squamulata Waterhouse, 1875), Lepidiota sororia Moser, 1913, Lepidiota suavior Blackburn, 1912 (= Lepidiota delicatula Blackburn, 1888), Lepidioderma albohirtum Waterhouse, 1875 (Dermolepida albohirtum), Microrhopaea flavipennis Lea, 1920, Rhopaea assimilis Blackburn, 1911, Rhopaea callabonnensis Blackburn, 1894 (Pararhopaea callabonnensis), Rhopaea consanguinea Blackburn, 1911 (Antitrogus consanguineus), Rhopaea dubitans Blackburn, 1911 (= Antitrogus mussoni (Blackburn, 1892)), Rhopaea hirtuosa Blackburn, 1898, Rhopaea incognita Blackburn, 1911 (= Antitrogus morbillosus (Blackburn, 1898)), Rhopaea laticollis Blackburn, 1911, Rhopaea morbillosa Blackburn, 1898 (Antitrogus morbillosus), Rhopaea mussoni Blackburn, 1892 (Antitrogus mussoni), Rhopaea soror Blackburn, 1892 (= Rhopaea heterodactyla (Germar, 1848)), and Zietzia geologa Blackburn, 1894. The presumed type of Lepidiota consobrina Girault, 1918 is shown not to be from the type locality, and syntypes of Othnonius batesii Olliff, 1890, Rhizotrogus tasmanicus Burmeister, 1855 (Antitrogus tasmanicus), and Rhopaea verreauxii Blanchard, 1851 and the lectotype of Melolontha heterodactyla Germar, 1848 (Rhopaea heterodactyla) could not be located. The remaining species-level taxa either have had lectotypes designated previously or have valid holotypes. Paratypes or paralectotypes are also indicated for some species.